2016
DOI: 10.1155/2016/6197867
|View full text |Cite
|
Sign up to set email alerts
|

Copyrolysis of Biomass and Coal: A Review of Effects of Copyrolysis Parameters, Product Properties, and Synergistic Mechanisms

Abstract: Concerns in the last few decades regarding the environmental and socioeconomic impacts of the dependence on fossil fuels have resulted in calls for more renewable and alternative energy sources. This has led to recent interest in copyrolysis of biomass and coal. Numerous reviews have been found related to individual pyrolysis of coal and biomass. This review deals mainly with the copyrolysis of coal and biomass and then compares their results with those obtained using coal and biomass pyrolysis in detail. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 77 publications
1
40
0
6
Order By: Relevance
“…This result suggested that sludge was decomposed more easily than low‐rank coal during the HT process. The weak covalent bonds in sludge may be easily broken under the thermal hydrolysis condition, and some organic compounds and mineral salt are dissolved in the liquid products during the HT process . As shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…This result suggested that sludge was decomposed more easily than low‐rank coal during the HT process. The weak covalent bonds in sludge may be easily broken under the thermal hydrolysis condition, and some organic compounds and mineral salt are dissolved in the liquid products during the HT process . As shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Besides, the H/C ratio of HT solid products reduced quickly as the amount of sludge increased. Sludge linked mainly by the weak ether R–O–R bonds can be easily decomposed under the heat, but the cross‐linked structure of coal is mostly composed of stronger C=C bonds, which may be difficult to break during the HT process . Figure shows the gas yield under different HT conditions.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations